Tradisi Tionghoa dalam Kebudayaan Nasional Indonesia - Suwito, Benny (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2006)
For centuries Chinese people have migrated to the area known in modern history as Indonesia, mainly for economi purposes. This migration has ignited process of interaction with local people and cultures. Through marriages, for instance, Chinese people - who were mainly male as so few female joined the migration these particular people form some unique society, which is very much based on Chinese tradition in China mainland with close association with local culture. Apart from some political and social supression, this society survives and to some extent even contributes to the Indonesian cultural plurality. The author highlights some significant cultural performances which are well accepted in some areas of Indonesia, such as the celebration of Chinese New Year (Imlek), dances, puppet show and architecture in the presence of many Chinese houses of worship (kelenteng). The author indicates, that the presence of Chinese people clearly enriches Indonesian culture.